Alternatif Pembiayaan Pembangunan SAUM - Kusbiantoro, BS (Journal of Regional and City Planning, 2003)
Jakarta Metropolitan Area, which has more than 20 million inhabitants, should be supported by mass rapid transit system. The Master Plan for MRT development had been initiated more than 20 years ago; since then various studies and plans have been done as well. However, the MET system has not been materialized. One of the reasons is the government‘s limited fund This paper proposes an alternative financing scheme to develop the MRT system, for the government to give concession to private sector for funding and managing development of both MRT and land use along the MART corridor.